Addition of Calcined Na2B4O7 on the Synthesis of Li7La3Zr2O12 - Imam Shofid Alaih; Sidiq Fathonah; Khoirina Dwi Nugrahaningtyas; Fitria Rahmawati (Jurnal Kimia Sains dan Aplikasi, 2021)
Li7La3Zr2O12 (LLZO) is a garnet-type electrolyte for all-solid-state lithium-ion batteries (ASSB). It has good chemical and electrochemical stability against lithium and a relatively high ionic conductivity. However, the ionic conductivity needs to be further increased to provide a high specific capacity of the ASSB. Element doping into LLZO is an effort to increase molecular defect, known to enhance the conductivity. This research studied the effect of the Na2B4O7 addition on the LLZO synthesis, producing LLZBO(A). The investigation aims to understand whether the sodium ions dope into the LLZO structure during synthesis, or it is only B ions to enter into the structure. Therefore, another synthesis with B2O3 of B precursor was conducted for comparison (LLZBO(B)). The precursors were mixed stoichiometrically by following the formula of Li7-xLa3-xZr2-xBxNaxO12 (LLZBO, x= 0.15; 0.20; 0.30). XRD analysis equipped with Le Bail refinement found that LLZBO(A) and LLZBO(B) mainly consist of cubic and tetragonal LLZO with a %mol of 69.06 – 69.84 %, and the main secondary phase is La2Zr2O7. The surface morphology of LLZBO(A) and LLZBO(B) is almost similar to the irregular form of large aggregates. The particles become more dispersed when 0.3 %mol dopant was submitted. Impedance analysis found a high ionic conductivity of LLZBAO(A)0.3 1.042x10-3 Scm-1.